Chloramphenicol Derivatization in Its Primary Hydroxyl Group with Basic Amino Acids Leads to New Pharmacophores with High Antimicrobial Activity - Artemis Tsirogianni; Georgia G. Kournoutou; Maria Mpogiatzoglou; George Dinos; Constantinos M. Athanassopoulos (MDPI AG, 2023)
In a previous study published by our group, successful modification of the antibiotic chloramphenicol (CHL) was reported, which was achieved by replacing the dichloroacetyl tail with alpha and beta amino acids, resulting in promising new antibacterial pharmacophores. In this study, CHL was further modified by linking the basic amino acids lysine, ornithine, and histidine to the primary hydroxyl group of CHL via triazole, carbamate, or amide bonding. Our results showed that while linking the basic amino acids retained antibacterial activity, it was somewhat reduced compared to CHL. However, in vitro testing demonstrated that all derivatives were comparable in activity to CHL and competed for the same ribosomal binding site with radioactive chloramphenicol. The amino acid-CHL tethering modes were evaluated either with carbamate (7, 8) derivatives, which exhibited higher activity, or with amide- (4-6) or triazole-bridged compounds (1-3), which were equally potent. Our findings suggest that these new pharmacophores have potential as antimicrobial agents, though further optimization is needed.